Fabrication of thermal enduring FBG sensor based on thermal induced reversible effect - Gunawardena, D.S.; Lai, M.H.; Lim, Kok Sing; Malekmohammadi, A.; Ahmad, Harith (Elsevier, 2016)
In this study, the thermal degradation of a fiber Bragg grating written on hydrogen loaded photosensitive Germanium/Boron co-doped fiber with 193 nm ArF excimer laser is investigated. A noteworthy increase in the grating reflectivity during annealing at 425 °C is observed indicating a thermal induced reversible effect deviating from the general thermal decay behavior. Both stepwise and continuous annealing procedures indicate a similar trend in the accelerated aging characteristics when analyzed with respect to demarcation energy (Ed). In the characterization of the lifetime of the treated FBG, a thermal sustainability of thousand years with less than 2% decay resulting in a grating reflectivity of 98% is observed at 300 °C for a grating as short as 10 mm. The ease of characterization and obtaining detailed information through the analysis of transmission spectra is also considered as an advantage in this study. These thermal enduring FBG sensors based on thermal annealing over a temperature range of 200–400 °C lay the foundation for a new direction of research in the investigation of durable temperature sensors.